Analysis of The Concept of Symbolism and Identity to Improve Image Higher Education (Case Study of Surabaya State University) - Ramadhan Maruta Pradana, Muhammad Sholeh, Mohamad Sulton Arifin, Nuning Triana, Devi Purnamasari Sas (Journal of Educational Studies, 2025)
The image of higher education institutions is greatly influenced by the power of symbolism and identity. This study aims to analyze the symbolic meaning and visual identity of Surabaya State University (Unesa) through a review of its logo and tagline, “Selangkah Lebih Maju” (One Step Ahead). The research method used is a qualitative approach with a literature study method, which involves collecting data from books, journals, institutional reports, and official Unesa documents. The results of the analysis show that the visual elements in the Unesa logo, such as the garuda wings, open book, hero monument, and lotus bud, have semiotic meanings that describe the values of nationality, science, and progress. Meanwhile, the tagline “One Step Ahead” serves as a verbal identity that affirms the institution's progressive and innovative orientation. In conclusion, the synergy between visual symbolism and verbal taglines strengthens Unesa's image as a dynamic, excellent, and highly competitive university.